1995
DOI: 10.1111/j.1464-5491.1995.tb00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria as Identified by a Spot Morning Urine Specimen in Non‐insulin‐treated Diabetes: an Eight‐year Follow‐up Study

Abstract: This study followed up a cohort of patients with microalbuminuria identified on a spot morning urine sample 8 years earlier and aimed to determine if a spot morning urinary albumin concentration was able to identify patients with non-insulin treated diabetes at increased risk of mortality and progression to nephropathy. In 1984, 47 of 216 patients chosen by random selection from our teaching hospital-based diabetes clinic were identified as having microalbuminuria (urinary albumin concentration 35-300 microgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Our finding that proteinuria alone predicted CVD is also in accord with findings from other studies [1][2][3][4][5][6][7][8][9][10][11][12]. Microalbuminuria has been shown to be related to insulin resistance and hyperinsulinaemia [35][36][37][38][39], and other components of metabolic syndrome, including blood pressure [40,41], high levels of triglycerides and apolipoprotein B [42,43] and obesity [44].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that proteinuria alone predicted CVD is also in accord with findings from other studies [1][2][3][4][5][6][7][8][9][10][11][12]. Microalbuminuria has been shown to be related to insulin resistance and hyperinsulinaemia [35][36][37][38][39], and other components of metabolic syndrome, including blood pressure [40,41], high levels of triglycerides and apolipoprotein B [42,43] and obesity [44].…”
Section: Discussionsupporting
confidence: 91%
“…Microalbuminuria and proteinuria predict cardiovascular disease (CVD) events, not only in diabetic [1][2][3][4][5][6][7], but also in non-diabetic individuals [5,[8][9][10][11][12]. Microalbuminuria was included in the WHO definition of the metabolic syndrome in 1998 [13], but since then there has been debate about microalbuminuria as a component of the metabolic syndrome [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, these events were similarly predicted by UAC and 24-h UAE. Two case-controlled studies evaluated UAC measured in a random sample (Beatty et al, 1994;Beatty et al, 1995) and a positive association of high UAC values with DN was demonstrated. However, these studies did not evaluate the relationship of UAC with GFR, as performed in the present cohort.…”
Section: Discussionmentioning
confidence: 97%
“…UAC in a random urine specimen may be an alternative for the diagnosis of microalbuminuria in diabetic patients, especially considering its low cost and accuracy (Incerti, Camargo JL, Gross, & Azevedo, 2005). Data on the predictive role of albuminuria were based mainly on 24-h urine collections or non-random samples (Heerspink et al, 2008;Heerspink et al, 2010;Hillege et al, 2002;Hovid et al, 2004;Mogensen, 1984;Mogensen & Christensen, 1984;Parving, Oxenboll, Svendsen, Christiansen, & Andersen, 1982;Steinke, Sikaiko, & Kramer, 2005;Viberti, Hill, Jarrett, Argyropoulos, Mahmud, & Keen, 1982;Zandbergen et al, 2007) and few studies assessed in patients with diabetes the role of spot urine collections (Beatty, Ritchie, Bell, Hadden, Kennedy, & Atkinson, 1995;Beatty, Ritchie, Hadden, Kennedy, Bell, & Atkinson, 1994;Incerti et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Urinary albumin concentration was measured at Århus University Hospital by a polyethylene glycol radioimmunoassay. Spot urinary albumin concentration is of value in predicting both progression of renal involvement and increased mortality, as is albumin excretion rate [26]. …”
Section: Methodsmentioning
confidence: 99%